ESG Disclosure and Accountability Practices in Women-led Social Enterprises - Khabibah, Nibras Anny; Susilo, Ghina Fitri Ariesta; Manurung, Herlina (Jati: Jurnal Akuntansi Terapan Indonesia, 2026)
The study examines ESG disclosures in two women-led Indonesian Social Enterprises (SEs), namely Kumpul Impact and Libu Perempuan, and how these disclosures shape accountability and legitimacy. Drawing on Legitimacy Theory, particularly the distinction between moral and pragmatic legitimacy, this study employed a comparative case study design, using five key informants from both SEs. Technically, data were collected through semi-structured interviews, analyzed with thematic analysis, complemented by document review and discourse analysis. The findings show that ESG disclosures serve as a legitimacy-building mechanism for SEs to negotiate stakeholders’ expectations with their own. Accordingly, Kumpul Impact adopts a pragmatic approach, emphasizing innovation, partnerships, and measurable sustainability outcomes. At the same time, Libu Perempuan focuses on relational accountability through culture and a strong relational orientation towards care, safety, and collective protection, reflecting a narrative- and trust-building approach rather than a compliance-based one. Theoretically, this study extends the application of Legitimacy Theory by demonstrating that women-led SEs build legitimacy through interwoven moral and pragmatic strategies. Practically, it proposes ESG practices with standards that are flexible and gender-responsive in relation to each other's relational accountability. This research provides an insight into the potentially hidden or neglected portions of the ESG standards' relational accountability perspective.